Thermal hydraulic analysis of the effect of emergency safety procedures for mitigation of accident conditions of pressurized water reactor nuclear power plants - Ibrahim, Said. M. A.; Atia, Sami. I. (International Journal of Engineering and Technology, 2018)
The prime objective of the nuclear safety is the complete prevention of the release of radioactive materials anywhere. One of the great concerns to the public is the nuclear safety of nuclear power reactors, especially after the two catastrophic accidents of Chernobyl and Fukushima. If a nuclear power plant (NPP) accident occurs, it is difficult to protect the environment and public from the radiation exposure. The safety systems performance of the nuclear plants is a very vital and decisive factor in enhancing the use of nuclear energy. The present research work offers thermal hydraulic simulation analysis of loss of coolant accident and station blackout conditions of a pressurized water reactor (PWR). In this study, the thermal hydraulic is performed by using RELAP and PCTran codes to establish a model of this PWR which could simulate its primary system, with good accuracy in the case of loss of coolant accident and station blackout conditions. These simulations depict the thermal hydraulic analysis and the verification of the response and efficiency of the accident management procedures in make certain that adequate, efficient, and effective emergency core cooling and auxiliary cooling safety systems are sufficient to submit a powerful cooling capacity of the reactor core in the case of accident conditions and that it makes an active contribution to the mitigation of the significant undesirable consequences, and the importance of the emergency and auxiliary safety systems during the accident conditions.